Tugas Pembinaan Dalam Ekstrakulikuler Bidang Seni Tari (Tari Rentak Bulian) di Sma Ylpi Pekanbaru Provinsi Riau T.A 2025/2026 - Siska Dewi; Nurmalinda (Yayasan Al-Afif, 2026)
This study aims to describe the coaching duties of the Rentak Bulian Dance extracurricular program at SMA YLPI Pekanbaru, Riau Province, Academic Year 2025/2026. Extracurricular activities serve as a means of developing students’ talents, interests, skills, and character outside regular classroom learning. Rentak Bulian Dance was chosen as the learning material because it is one of Riau’s traditional dances that contains important cultural values and deserves preservation. This research employed a descriptive qualitative method. The research subjects consisted of one dance extracurricular coach, Izadri, S.Pd., Gr., and eight students participating in the Rentak Bulian Dance extracurricular program. Data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, conclusion drawing, and verification. Data validity was ensured through source, technique, and time triangulation. The findings are expected to describe the coach’s responsibilities in planning activities, guiding practice sessions, conducting evaluations, managing administration, and organizing performances. In addition, the extracurricular coaching program is expected to improve students’ dance skills, self-confidence, discipline, and appreciation of local culture. This study is expected to provide useful input for schools and educational institutions in developing more effective dance extracurricular programs and supporting the preservation of Riau Malay culture